The Awareness of Junior High School Students in Malang Towards Online Learning: Post-Pandemic Effect - Citra Kurniawan; Shirly Rizki Kusumaningrum; Deka Dyah Utami; Agus Sholeh; Zuhkhriyan Zakaria (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Online learning was one of the preferred learning strategies during the COVID-19 pandemic. Changes in learning orientation that was very fast with little coercion due to the limitations of face-to-face learning make educational institutions design appropriate learning strategies. Students as one learning component certainly try to adjust their activities in online learning. The process of adapting to online learning often causes failure in the learning process because of their unpreparedness for online learning. Finding a suitable role model in the process of adapting to online learning was a problem in this study. This study aims to design student models in online learning during the learning process. This study method uses a data visualization approach with data mining and involves as many as 350 students from various junior high schools in Malang. The results showed that there were differences in students' tendencies towards the choice of online learning platforms. In addition, skills in using technology are a determining factor in the formation of student profiles. Implementation of study results is one of the keys to the development of online learning in the future.